Permeability-Enhancing and Protective Effect on Small Intestine of Punicic Acid in Different Forms and Their Nanoemulsions With Low Toxicity - Duan D; Xie H; Jiang J; Yang P; Guo Z; Guo X; Chen X; Yao Q (International Journal of Nanomedicine)
Dongyan Duan,1,* Hua Xie,2,* Jiayi Jiang,1 Ping Yang,1 Zhiyuan Guo,2 Xiaoqiang Guo,1 Xingyu Chen,1 Qian Yao1 1Key Laboratory of Medicinal and Edible Plants Resources Development of Sichuan Education Department, Sichuan Industrial Institute of Antibiotics, School of Pharmacy, Chengdu University, Chengdu, 610106, People’s Republic of China; 2Sichuan Provincial Institute for Drug Control and Research, Chengdu, 610000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qian Yao, School of Pharmacy, Chengdu University, Shiling Town, Longquan District, Chengdu, Sichuan Province, 610106, People’s Republic of China, Email yaoqian@cdu.edu.cnPurpose: Most absorption enhancers boost the oral absorption of drugs via increasing intestinal permeability. However, they often damage intestinal mucosa and induce inflammatory reactions. The aim of this study is to synthesize a new absorption enhancer, punicic acid ethyl ester (PAEE), with excellent absorption-prompting effect and low toxicity.Methods: The structure of PAEE was confirmed by NMR, MS, IR and UV. Setting oleic acid (OA) as the control, the three forms of punicic acid (PA), ie, free PA, PAEE, and pomegranate seed oil, in which PA exists in the form of triglyceride, were formulated into nanoemulsions (NE). The stability, physiochemical properties of the oils and NE were compared. The permeation-enhancing effect was estimated by phenol red intestinal transport experiments. The potential damage on small intestines was assessed by biochemical assay and pathological section.Results: Though the three forms of PA had various strength in enhancing intestinal permeability, the difference was not significant (p > 0.05). Moreover, the effect was notably stronger than that of OA (p < 0.05) and was inversely related to the density and required HLB value of the oils. Compared to the corresponding oils, the NE exhibited much weaker effect in prompting intestinal permeability. Oral administration of OA and OA NE for 10 d impaired intestinal mucosa and villi along with strong inflammatory reactions in the small intestines. In contrast, the oils from PA series and their NE did not induce obvious intestinal inflammation. PAEE and its NE hindered the release of cytokines and increased the ratio of intestinal villus length to crypt depth.Conclusion: PAEE is a promising absorption enhancer with a strong permeability-prompting effect and mucosa-protecting capacity against intestinal inflammation. It provides a practical strategy to enhance the bioavailability of the drugs with poor biological membrane penetration. Keywords: punicic acid, punicic acid ethyl ester, pomegranate seed oil, nanoemulsions, permeability-enhancing effect